Effect of Virtual Reality on Dental Pain in Children during Local Anesthesia Administration - Arwa Abdulrhman Bakhaider; Arwa Ali Beshlawi; Marwah Salah Alsoufi; Taghreed Kamel Alhashmi Alamer; Maram Mohammed Morshed Senan; Shanthi Vanka; Amit Vanka; Othman Wali (Wolters Kluwer Medknow Publications, 2024)
Background: Dental procedures often generate anxiety and fear in children. Virtual reality (VR) is a novel method of distraction for behavior management during dental treatment. Aim: To evaluate the effect of using VR eyeglasses on anxiety/pain during local anesthesia (LA) administration for children. Materials and Methods: Children aged 6-12 years, rated to be Frankl +(positive) or −(negative) without any systemic background were included. Children receiving inferior alveolar nerve block anesthesia were randomized into two groups: Control group (n = 20) exposed to Tell-Show-Do (TSD) alone and study group (n = 20) exposed to TSD with VR through the use of head-mounted immersive type of display powered by a smartphone VR box. Oxygen saturation (SpO2), pulse rate (PR), and anxiety/pain were monitored preoperatively, during LA administration and postoperatively. Results: SpO2 showed no significant difference between the groups, whereas PR and perceived pain levels were significantly different between the groups. Conclusions: PR and pain scores were reduced with the use of VR in children during the administration of LA. VR can be an effective tool in managing behavior of children rated Frankl positive and negative.